2006
DOI: 10.1177/014860710603000297
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hyperglycemic Hyperinsulinemia on Small‐Intestinal Mucosal Protein Synthesis in Patients After Surgical Stress

Abstract: Hyperglycemic hyperinsulinemia cannot stimulate intestinal protein synthesis in healthy individuals but does so in conditions characterized by an altered somatotropic axis such as diabetes. Only in a state of growth hormone resistance (high growth hormone but low insulin like growth factor [IGF‐1] concentrations), extra insulin may acutely reverse the impaired, growth‐hormone‐induced IGF‐1 release, thereby exerting anabolic actions at the intestinal tract. Growth hormone resistance can be also found in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Insulin may be responsible for the effect of maltodextrins, because insulinemia was similarly increased in both arms in the current study. However, previous studies reported that insulin did not influence the intestinal protein synthesis rate in healthy conditions (25,36), in contrast with observations made in surgical patients (37).…”
Section: Discussionmentioning
confidence: 62%
“…Insulin may be responsible for the effect of maltodextrins, because insulinemia was similarly increased in both arms in the current study. However, previous studies reported that insulin did not influence the intestinal protein synthesis rate in healthy conditions (25,36), in contrast with observations made in surgical patients (37).…”
Section: Discussionmentioning
confidence: 62%
“…In addition to effects on motility, elevated glucose-dependent insulinotropic polypeptide secretion could stimulate pancreatic insulin secretion. Hyperinsulinaemia can have anabolic actions on the intestinal tract, with a demonstrated stimulation of ileal protein synthesis following ileostomy (Rittler et al 2006) and specific reduction of urinary Na + excretion (Quinones-Galvan & Ferrannini, 1997), so addressing the underlying issue of Na + depletion. Thus, although the exact 'trigger' for intestinal adaptation remains to be determined, adaptation does indeed take place, enabling the remaining absorptive surface of the GI tract and transit time to increase, both of which enhance the process of absorption and Na-water balance.…”
Section: General Hyperplasiamentioning
confidence: 99%